Obsidian distribution from a Lapita cemetery sheds light on its value to past societies. Issue 2 (3rd July 2015) - Constantine, Anne; Reepmeyer, Christian; Bedford, Stuart; Spriggs, Matthew; Ravn, Mads
Abstract: The Teouma site on Efate Island in Vanuatu is unique in the Pacific, as it enables us to analyse an archaeological assemblage in relation to discrete activity areas of burial and settlement at the time of initial settlement of the archipelago. Geochemical sourcing of obsidian in combination with a basic technological analysis help us to understand whether differences exist between burial zones and settlement middens. The results show that the distribution of obsidian was not directly associated with individual burials and does not unambiguously correlate with specific activity areas, thus questioning the hypothesis that obsidian transportation was linked to the increase in individual status. It is argued that the evidence adds further weight to those models that interpret the function of obsidian as being associated with past social transactions or relationships, rather than having any enduring or intrinsic value as a wealth‐enhancing commodity.